Internet skills and the digital divide - van Deursen, Alexander; van Dijk, Jan (New media & society, 2011)
Because of the growing amount of information on the internet and people’s increasing dependence on information, internet skills should be considered as a vital resource in contemporary society. This article focuses on the differential possession of internet skills among the Dutch population. In two studies, an in-depth range of internet skills are measured by charging subjects assignments to be accomplished on the internet. Subjects were recruited by applying a random stratified sampling method over gender, age, and education. While the level of operational and formal internet skills appeared quite high, the level of information and strategic internet skills is questionable. Whereas education appeared an important contributor to all skill levels, age only appeared a significant contributor to operational and formal skills. The results strengthen the findings that the original digital divide of physical internet access has evolved into a divide that includes differences in skills to use the internet.